208k views
3 votes
What is the answer to 5(m−7)+3(m+9)=6

2 Answers

7 votes

Answer:m

=

2.14

Explanation:

Begin by using the distributive property to simplify. Here is a helpful image if you need a refresher on the distributive property:

User Hutabalian
by
5.7k points
6 votes

Answer:

m =

7/4

Explanation:

Step 1: Simplify both sides of the equation.

5(m−7)+3(m+9)=6

(5)(m)+(5)(−7)+(3)(m)+(3)(9)=6 (Distribute)

5m+−35+3m+27=6

(5m+3m)+(−35+27)=6 (Combine Like Terms)

8m+−8=6

8m−8=6

Step 2: Add 8 to both sides.

8m−8+8=6+8

8m=14

Step 3: Divide both sides by 8.

Cheers! :)

User Kgorskowski
by
6.4k points